Features of postoperative healing after osteoplasty of alveolar applications in patients with a galvanic pathology - Tymofeiev Александр Алексеевич; Kogut Владимир Любомирович (Actual Dentistry, 2020)
Purpose. The features of healing of postoperative wounds after osteoplasty of alveolar processes of jaws with the use of titanium and bioresorbable membranes in patients with galvanic pathology were studied. Methods. There were examined 120 patients, aged 19 to 35 years, with or without metal dentures. In the course of surgical preparation of alveolar processes of jaws for further dental implantation (osteoplasty of alveolar processes), bioresorbable membranes based on polylactic acid and membranes made of titanium were used. Depending on the presence or absence of galvanic pathology, all patients were divided into 4 groups. Results. It was found that in patients without galvanic pathology, postoperative healing occurs without inflammatory complications. In patients with galvanic (compensated and/or decompensated form) in the early postoperative period, 51.6 % of the examined patients appeared complications in the form of severe pain and other inflammatory complications. In patients with galvanosis (atypical and typical forms) both early (82.8 %) and late (10.4 %) postoperative complications occurred in the postoperative period. All postoperative complications were equally common in the subjects who were using titanium membranes and in patients with bioresorbable membranes. Conclusions. It was established that in the presence of non-removable metal dentures in the oral cavity made of base of ignoble metal alloys, leading to the development of galvanism or galvanosis, there are early and late inflammatory complications in the preparation of alveolar processes for dental implantation, which significantly prolongs the time of healing of postoperative wounds.